Farinhas de ora-pro-nóbis: Aplicação em massas alimentícias e avaliação do efeito de secagem - Berto, Ismaiara Rodrigues (2023)
The food market has sought to innovate to meet the demands of the population. Vegetable-based products are highly exploited due to their nutritional composition. In this sense, it is important to diversify crops with new alternatives in order to reduce the negative impact on the environment. The cacti of the Pereskia genus are unconventional food plants (PANCs) with significant nutritional properties, especially Pereskia aculeata and Pereskia grandifolia, better known as ora-pro-nóbis. In addition to their high nutritional value, ora-pro-nóbis have significant antioxidant capacity due to their phytochemical composition, which attributes them to nutraceutical use and the production of drugs. The leaves of P. aculeata and P. grandifolia have a digestibility of around 85%, and the proteins have a diverse composition of essential amino acids. Ora-pro-nóbis flours have been used in the formulation of food products, helping to supplement protein, mineral, fiber and antioxidant compound content. The aim was to produce pasta, a traditional, accessible and practical product that is rich in carbohydrates and concentrations, but lacks in terms of protein. With this in mind, the aim was to evaluate the technological potential of ora-pro-nobis flour applied to spaghetti noodles and to assess the effect of drying the flours. The flours were obtained by drying the leaves of two different species at a temperature of 60 °C. The flours were then assessed for nutritional, physical and chemical parameters. Five formulations were made with 0, 1, 3, 5 and 7% ora-pro-nobis flour applied to noodles. After preparation, physicochemical and cooking analyses were carried out. The ora-pro-nobis flours have adequate nutritional and physico-chemical quality and are safe for consumption, with high levels of protein, minerals, phytochemical compounds and low moisture content. The potential of the flours applied to noodles increased the protein, fiber, ash and lipids content of the samples, especially the Pereskia aculeata flours. The ora-pro-nóbis has potential for nutritional supplementation, with high nutrient contents and properties that allow it to be consumed in natura, in the form of flours or in the formulation of new products, in a safe and quality manner.